If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -6x = 7x + -10 + 3 Reorder the terms: 6 + -6x = -10 + 3 + 7x Combine like terms: -10 + 3 = -7 6 + -6x = -7 + 7x Solving 6 + -6x = -7 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 6 + -6x + -7x = -7 + 7x + -7x Combine like terms: -6x + -7x = -13x 6 + -13x = -7 + 7x + -7x Combine like terms: 7x + -7x = 0 6 + -13x = -7 + 0 6 + -13x = -7 Add '-6' to each side of the equation. 6 + -6 + -13x = -7 + -6 Combine like terms: 6 + -6 = 0 0 + -13x = -7 + -6 -13x = -7 + -6 Combine like terms: -7 + -6 = -13 -13x = -13 Divide each side by '-13'. x = 1 Simplifying x = 1
| 3/4x-2y=15 | | -7x+5=2x-10.1 | | 2(1-4x)=3(3x+5) | | 3(4x-7)=5(3x+3) | | 4x^2+20=20x | | 30=4.9x^2+15x+30 | | 5x-32-11x=22 | | 8x-17-25x=12x+5x-34 | | 6(2x+4)=4(4x+7) | | a^4-2a^2b^2+b^4= | | 7c/2c | | 7x+(5x+3)=5(x-3)+2 | | 7f=28 | | a^4-2a^2+b^4= | | x-5x+22=70 | | 5x-(2x+13)=14 | | -3x+5(3x+2)=-3(7x+4)+3x+2 | | 5(3x-8)+3(7x+6)=6(8x-3)-4(2x+5) | | -4=y/4 | | 10=2h+6 | | X^2-41x+24=0 | | 5(3x-8)*3(7x+6)=6(8x-3)-4(2x+5) | | 5.9p+0.3p+7.1=-2.2 | | -12x+5=-x+6 | | f(1/4)=1/16-1/4+3 | | 15n-9n-15=0 | | -12x(5)=-x(6) | | 5.3-3c+15=16.84 | | 5x+3+4x+3x-3=180 | | 1.7q-5.4-4.9q=-4.2-3.5 | | 3n+20=180-(4n-20) | | 4p-25/2=6 |